Perspectives in the Recycling of High Sulphatized Electrodes from Lead Acid Batteries. (13th June 2021) - Mihaila, L.; Unguresan, M.; Rada, M.; Popa, A.; Macavei, S.; Vermesan, H.; Rada, S.
Abstract: The structural modifications of the infrared (IR) bands induced by the CuO and MnO2 addition in the recycled Pb-PbO2 host matrix are due to the bending modes of Pb-O-Pb linkages, the decrease of intensity of sulfate ions and the random intercalation of the [CuO n ] and [MnO n ] structural units. Electron paramagnetic resonance (EPR) measurements show that the copper ions exist in two stable valence states as Cu +1 and Cu +2 ions. The cyclic voltammogram of the electrode containing 5 mol % CuO does not show hydrogen evolution reactions and produces a removal of passivation phenomena by an increase in the residual current across the potential range between 0 and 2 V.